The Influence of the Food and Drug Administration Pregnancy and Lactation Labeling Rule on Drug Information Resources. Issue 4 (April 2021) - Harris, John Brock; Holmes, Amy P.; Eiland, Lea S.
Background: Drug information resources are commonly used by health-care providers answering pregnancy-related medication questions. In 2015, the United States Food and Drug Administration approved a new pregnancy and lactation medication labeling content and format, removing the pregnancy category, and using a narrative. Despite labeling requirements changing, it is unknown if drug information resources updated monographs to reflect these changes. Objective: The primary objective was to evaluate if commonly used drug information resources provide pregnancy information listed similar to the requirements of the Pregnancy and Lactation Labeling Rule (PLLR). Secondary analyses included evaluating the references and inclusion of the pregnancy category rating. Methods: Pregnancy recommendations for 23 medications were evaluated in 9 drug information resources (Clinical Pharmacology, Drugs in Pregnancy and Lactation, Epocrates®, First Databank, LexiComp® Online, LexiComp® Online Pregnancy & Lactation, In-Depth, Medi-Span®, Micromedex®, and Multum®). The number of references per drug monograph and most recent reference publication year was obtained. Results: LexiComp® Online Pregnancy & Lactation, In-Depth mimics the new PLLR structure and consistently had the highest number of and most recent references when the medication was included. Drugs in Pregnancy and Lactation was the next most similar in content with the PLLR and second in most references per monograph; however, the most recent reference was the textbook publication year. Conclusion and Relevance: LexiComp® Online Pregnancy & Lactation, In-Depth and Drugs in Pregnancy and Lactation provided pregnancy information in a format most similar to the PLLR. However, several drug information resources contained pregnancy categories ratings that were to be removed from medication labeling per the PLLR.